Haiti : Request for Extension of the Arrangement Under the Poverty Reduction and Growth Facility; Staff Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
According to the fifth review of the Poverty Reduction and Growth Facility (PRGF) arrangement, the Haitian authorities remain committed to macroeconomic stability under the program. On completion of the fifth review of the PRGF, they requested a new three-year Extended Credit Facility (ECF) arrangement to help sustain economic growth and to preserve macroeconomic stability. The IMF Board approved a three-year arrangement for Haiti under the PRGF. This will help ensure that endorsement of policy measures to preserve macroeconomic stability and sustain growth in Haiti can be undertaken before the current PRGF expires.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Government Policy; International Lending and Debt Problems; Provision and Effects of Welfare Program; Haiti